2020
DOI: 10.1371/journal.pone.0231336
|View full text |Cite
|
Sign up to set email alerts
|

A population-specific low-frequency variant of SLC22A12 (p.W258*) explains nearby genome-wide association signals for serum uric acid concentrations among Koreans

Abstract: Prolonged hyperuricemia is a cause of gout and an independent risk factor for chronic health conditions including diabetes and chronic kidney diseases. Genome-wide association studies (GWASs) for serum uric acid (SUA) concentrations have repeatedly confirmed genetic loci including those encoding uric acid transporters such as ABCG2 and SLC9A2. However, many single nucleotide polymorphisms (SNPs) found in GWASs have been common variants with small effects and unknown functions. In addition, there is still much … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Using a population-specific genotyping array and a population-matching imputation panel, we were able to obtain highly accurate genotypes which led to the discovery of several novel GWAS variants, especially at low AF. Finding low-frequency coding variants with large effects has recently been a concern of GWAS, and some successful cases have been reported ( 45 48 ). Protein-altering variants affecting certain phenotypes are crucial in understanding pathophysiology and can be directly linked to treatment ( 26 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Using a population-specific genotyping array and a population-matching imputation panel, we were able to obtain highly accurate genotypes which led to the discovery of several novel GWAS variants, especially at low AF. Finding low-frequency coding variants with large effects has recently been a concern of GWAS, and some successful cases have been reported ( 45 48 ). Protein-altering variants affecting certain phenotypes are crucial in understanding pathophysiology and can be directly linked to treatment ( 26 , 49 ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the same mutant URAT1 allele (W258X) was found in studies of individuals with hypouricemia in Korea and this was also the most prevalent (57%) mutant URAT1 allele in the Korean population [ 26 ]. Haplotype analysis of the W258X mutant allele was also performed in the Korean population [ 28 ], and this showed that the mutant W258X allele was associated with the same haplotype in Korea as in Japan. However, it cannot be concluded that the origin of the W258X allele is common to Japan and Korea because different sets of genetic markers were used in the studies in Japan and Korea.…”
Section: Genetic Basis For the Differing Prevalence Of Renal Hypouric...mentioning
confidence: 99%